41. THE PREVALENCE OF OSTEOPOROSIS IN WOMEN OVER 45 AND MEN OVER 50 SEEKING MEDICAL EXAMINATION AND TREATMENT AT TAN CHAU GENERAL HOSPITAL IN 2023 (Vietnam Journal of Community Medicine, 2024)
Objective: Describe the current situation of osteoporosis and analyze some factors related to osteoporosis in women over 45 years old and men over 50 years old who came for medical examination and treatment at Tan Chau Regional General Hospital in 2023.Subject and methods: The study was conducted on 168 patients, including women over 45 and men over 50, who sought medical examination and treatment at Tan Chau General Hospital from March 2023 to October 2023. The sample was selected based on criteria, with a higher proportion of women (77.4%) compared to men (22.6%). The age group over 65 years (39.9%) was the largest, while the 46-55 age group (21.4%) was the smallest.Results: The prevalence of osteoporosis (54.2%) is quite close to the percentage of those without it (45.8%). According to World Health Organization classification: normal (45.8%) and osteopenia (29.2%), severe osteoporosis (0.6%) and osteoporosis (24.4%). The risk of fractures (according to the FRAX model) is 58.3%. The results indicate a significant correlation between age group and osteoporosis status, with the > 65 years group (50.5%) being significantly higher than the 55-65 years group (30.8%) and the > 45 to 55 years group (18.7%) with p = 0.008, indicating that this difference is statistically significant. According to the study results, there is a correlation between occupation and osteoporosis status, with manual labor (37.4%) being significantly lower than non-manual labor (62.6%). The p-value = 0.000 indicates that this difference is statistically significant.Conclusions: 54.2% of the study participants had osteoporosis. Age group, occupation, educational level, menstrual status in women, and physical activity were all factors associated with osteoporosis among the study subjects.
Keywords: Osteoporosis; FRAX model